Regimes Militares e a Segurança Nacional no Cone Sul - Aguilar, Sérgio Luiz Cruz [UNESP] (My University, 2011)
The implantation of military regimes in South America, from the mid-1960s, happened in the context of the Cold War. As a result, both the occurrence of military coups and the plans and actions for the national defense of the Southern Cone States occurred following the logic of that period and the concept of hemispheric defense preached by the United States, with priority in combating the so-called internal subversion. Thus, the need to combat the “internal enemy” has led these countries to participate in hemispheric mechanisms or create his own arrangements for coordination. The article starts from the conflict hypothesis used by the military governments in their military planning to analyze the actions carried out against leftist movements, including coordination between the governments of the Southern Cone. The understanding of the defense concepts against Soviet communism allows us to understand that the groups placed against the military governments were seen as a danger to the State and, in that “state of war”, the means justified the ends.

A implantação dos regimes militares no Cone Sul, a partir de meados da década de 1960, aconteceu no âmbito da Guerra Fria. Em consequência, tanto a ocorrência dos golpes militares como os planejamentos e ações para a defesa nacional dos Estados da sub-região se deram seguindo a lógica daquele período e a concepção de defesa hemisférica pregada pelos Estados Unidos, com prioridade no combate a chamada subversão interna. Dessa forma, a necessidade de combater o “inimigo interno” levou os países a participarem de mecanismos hemisféricos ou criarem arranjos próprios de coordenação. O artigo parte das hipóteses de conflito utilizadas nos planejamentos dos governos militares para analisar as ações empregadas contra os movimentos de esquerda, incluindo a coordenação entre os governos do Cone Sul. O entendimento das concepções de defesa contra o “comunismo” soviético permite compreender que os grupos que se colocavam contra os regimes eram entendidos como um perigo ao Estado e, nesse “estado de guerra”, os meios justificavam os fins.
Keywords: Cone Sul; defesa nacional; regimes militares